2010
DOI: 10.4314/ijest.v2i1.59089
|View full text |Cite
|
Sign up to set email alerts
|

Flow field development in a direct injection diesel engine with different manifolds

Abstract: This paper reports a study on the effect of helical, spiral, and helical-spiral combination manifold configuration on air motion and turbulence inside the cylinder of a Direct Injection (DI) diesel engine motored at 3000 rpm. Three-dimensional model of the manifolds and the cylinder is created and meshed using the pre-processor GAMBIT. The flow characteristics of these engine manifolds are examined under transient conditions using Computational Fluid Dynamics (CFD) code STAR-CD. The predicted CFD results of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…A. D. Gosman, P. S. Harvey [4] analyzed fuel-air mixing and combustion in an ax symmetric direct injection diesel engine numerically. Benny Paul1 [5] reported a study on the effect of helical, spiral, and helical-spiral combination manifold configuration on air motion and turbulence inside the cylinder of a Direct Injection (DI) diesel engine motored at 3000 rpm. F. Payri [6] studied Three-dimensional flow calculations of the intake and compression stroke of a four-valve direct-injection Diesel engine have been carried out with different combustion chambers.…”
Section: Introductionmentioning
confidence: 99%
“…A. D. Gosman, P. S. Harvey [4] analyzed fuel-air mixing and combustion in an ax symmetric direct injection diesel engine numerically. Benny Paul1 [5] reported a study on the effect of helical, spiral, and helical-spiral combination manifold configuration on air motion and turbulence inside the cylinder of a Direct Injection (DI) diesel engine motored at 3000 rpm. F. Payri [6] studied Three-dimensional flow calculations of the intake and compression stroke of a four-valve direct-injection Diesel engine have been carried out with different combustion chambers.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that spiral-helical-shaped manifold creates higher swirl flow inside the cylinder than spiral manifold. Martins et al [2] performed a CFD study with modified helical inlet port under different value lifts using commercial CFD code Fluent and found that the increase in valve lift decreases the swirl number. It indicates that the valve position also plays an important role in the in-cylinder flows.…”
Section: Introductionmentioning
confidence: 99%
“…Swirling creation inside the engine was earlier studied by various researchers [1][2][3] by changing the parameters like manifold shape, combustion chamber configurations, and piston head shape. There are two ways of enhancing the combustion process thereby increasing the engine thermal efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A suitable turbulence level of the charge is obtained by the initial swirl and squish. The initial swirl in the cylinder is made by the intake system (Paul and Ganesan, 2010). The flow of charge in the radius direction inward the chamber is forced by squeezing the surface of the piston.…”
Section: Introductionmentioning
confidence: 99%